Pedagogy Theory and History Science in the Circle Students with from the Lesson Outside Processes Organization in Essence Innovation Approaches - Yunusova Dilorom Abdumajitovna (Scientific Trends, 2026)
This article discusses the issue of organizing extracurricular activities based on innovative approaches in teaching the subject "Theory and History of Pedagogy" in the higher pedagogical education system. The study analyzed the possibilities of ensuring the active participation of students in the independent learning process, connecting their theoretical knowledge with practice, as well as developing their professional and personal competencies. For this purpose, the effectiveness of using modern methods such as gamification, project-based learning, the flipped classroom model, pedagogical theater, and historical and pedagogical expeditions was studied.
Keywords: Gamification, project -based learning, flipped classroom model, cooperative learning, Pedagogical theater and staging, Historical-pedagogical expedition, virtual tour, SWOT analysis.